2010
DOI: 10.1007/s00294-010-0309-z
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional effect of a calmodulin inhibitor, W-7, on the ligninolytic enzyme genes in Phanerochaete chrysosporium

Abstract: We investigated the effects of a calmodulin (CaM) inhibitor, W-7, on the expression of lignin peroxidase (LiP) and manganese peroxidase (MnP) genes in Phanerochaete chrysosporium to consider the role of cam gene, which was upregulated in parallel with the total activities of LiP and MnP in our previous transcriptomic analysis. The addition of 100 μM W-7 to the fungal cultures repressed the total activities of LiP and MnP, whereas the addition of 100 μM W-5, which is a control drug of W-7, retained approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
3
14
1
Order By: Relevance
“…However, these results were inconclusive because Mn 2+ -dependent oxidation activity, which represents the total activity of MnP and VP, was the same in both strains (Yao et al 2013). In P. chrysosporium, our previous studies suggested that the CaM gene was induced by an increase of intracellular cAMP concentration (Minami et al 2007(Minami et al , 2009Sakamoto et al 2010Sakamoto et al , 2012 and that CaM positively regulates the expression of almost all genes encoding isozymes of LiP and MnP (Sakamoto et al 2010(Sakamoto et al , 2012. Because the present study suggested that cAMP also induces transcription of the CaM gene in P. ostreatus, similar to P. chrysosporium (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, these results were inconclusive because Mn 2+ -dependent oxidation activity, which represents the total activity of MnP and VP, was the same in both strains (Yao et al 2013). In P. chrysosporium, our previous studies suggested that the CaM gene was induced by an increase of intracellular cAMP concentration (Minami et al 2007(Minami et al , 2009Sakamoto et al 2010Sakamoto et al , 2012 and that CaM positively regulates the expression of almost all genes encoding isozymes of LiP and MnP (Sakamoto et al 2010(Sakamoto et al , 2012. Because the present study suggested that cAMP also induces transcription of the CaM gene in P. ostreatus, similar to P. chrysosporium (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…2). These results suggest that CaM negatively regulates MnP and VP activities in P. ostreatus, in contrast to the positive effect of CaM on MnP and LiP in P. chrysosporium (Sakamoto et al 2010). …”
Section: Effect Of Cam Inhibitors On Mnp Activitycontrasting
confidence: 56%
See 1 more Smart Citation
“…The CaM gene ( cam ) is present as a single isoform in the P. chrysosporium genome (Martinez et al 2004). We previously revealed that the CaM pathway is required for expression of lip and mnp genes in P. chrysosporium (Minami et al 2007; Minami et al 2009; Sakamoto et al 2010), but the relationship between these signaling factors that leads to LiP and MnP expression has remained unclear. Here, we report experimental results suggesting that CaM expression is regulated by the cAMP pathway, and that cAMP controls LiP and MnP expression mainly through regulation of CaM expression.…”
Section: Introductionmentioning
confidence: 99%
“…These expression profiles were similar to those of cultures with added atropine. It was hypothesized that atropine inhibits CaM signaling, thereby inhibiting cAMP signaling, or vice versa, to affect LiP and MnP production (Sakamoto et al 2010) (Fig. 1).…”
Section: Differential Gene Expression In Phanerochaete Species Grown mentioning
confidence: 99%